Cesarean scar pregnancy: Case report and review of the literature: Nosečnost v brazgotini po carskem rezu: prikaz primera in pregled literature - Dovnik, Andraž; Kores Testen, Polona; Mlakar, Lea; Reljič, Milan; Arko, Darja; Takač, Iztok (Acta Medico-Biotechnica, 2021)
Purpose: A cesarean scar pregnancy is a rare form of ectopic pregnancy in which the gestational sac is implanted in the uterine scar after a previous cesarean section. Early diagnosis is crucial, and transvaginal ultrasound is the most appropriate diagnostic tool. Different management options have been described in the literature; however, there is no consensus regarding optimal treatment due to the rarity of the condition. Case report: We present a case involving a cesarean scar pregnancy which was managed with hysterotomy due to the advanced stage of pregnancy (fetal crown–rump length = 3.5 cm). Conclusion: Early diagnosis of a cesarean scar pregnancy is important to avoid complications and to preserve fertility. Various treatment modalities have been described in the literature, including medical and surgical options.